Educational Activities of a Teacher from the Point of View of Humanitarian Methodology - Roganova, Мarina; Yatsenko, Victoria; Onischuk, Tatiana (My University, 2020)
The article examines the issues of educational activity of a modern teacher from the point of view of humanitarian methodology, which is based on the subject-subject relationship of the teacher and the pupil; states that the humanistic position of the educator presupposes the presence of deep knowledge about a person, about the laws of his development, his place in the world around him.
Roganova M. Educational Activities of a Teacher from the Point of View of Humanitarian Methodology / M. Roganova, V. Yatsenko, T. Onischuk // Вісник Луганського нац. ун-ту ім. Тараса Шевченка. Педагогічні науки. – 2020. – № 7 (338). –С. 84–94.
Keywords: навчальна діяльність, міждисциплінарний підхід, гуманітарна методологія, екзистенційна філософія, синергетика, акмеологія, герменевтика; educational activity, interdisciplinary approach, humanitarian methodology, existential philosophy, synergetics, acmeology, hermeneutics; учебная деятельность, междисциплинарный подход, гуманитарная методология, экзистенциальная философия, синергетика, акмеология, герменевтика